Postbiotics and their potential usage in the diet of young children - S.L. Nyankovskyy; О.S. Nyankovska; M.S. Yatsula; M.I. Horodylovska (Zaslavsky O.Yu., 2020)
The term "biotics" refers to nutritional strategies that can be utilized to direct the gut microbiota towards a more favorable state for host health. The term "biotic" is derived from the Greek word biōtikós, meaning "pertaining to life", and refers to the biological ecosystem made up of living organisms together with their physical environment. Prebiotics, probiotics and synbiotics can modulate the gut microbiota composition and its activity, and also have direct effects on the immune response. The newest member of the biotics family, postbiotics, are bioactive compounds produced by food-grade microorganisms during a fermentation process. Postbiotics include microbial cells, cell constituents and various metabolites. The effectiveness of postbiotics is based on microbial metabolites - proteins, lipids, carbohydrates, vitamins, organic acids, cell wall components or other complex molecules formed from the fermented matrix. Postbiotics have local and systemic effects. Local effects of postbiotics are immunomodulatory, anti-inflammatory, antimicrobial, intestinal barrier formation, effects on the microbiota composition and activity, systemic - antioxidant, antihypertensive, hypocholesterolemic, antiproliferative, anti-obesogenic. The results of gut microbiota research will help develop individual recommendations in terms of personalized nutrition or interventions to improve health. Postbiotics might be a safer alternative to probiotics in immunocompromised or severely ill children.